The effects of instructional leadership, PLC, and self-efficacy on teacher performance - Melda Hasna; Aslamiah Aslamiah; Novitawati Novitawati (Universitas Pendidikan Indonesia, 2025)
This study is motivated by the crucial role of teachers in determining the quality of education in schools, which is strongly influenced by school leadership, collaborative culture, and teachers’ self-efficacy. The purpose of this research is to analyze the effects of instructional leadership, Professional Learning Community (PLC), and self-efficacy on the performance of public junior high school teachers in Banjarmasin Timur District. A quantitative correlational design was used. The population consisted of 227 teachers, and the samples were obtained through proportional random sampling. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability. The data were analyzed using multiple linear regression, path analysis, and the Sobel test to examine mediation effects. The findings reveal that instructional leadership, PLC, and self-efficacy have significant effects on teacher performance, both partially and simultaneously. Self-efficacy is confirmed as a psychological factor that strengthens the role of instructional leadership and PLC in enhancing teacher performance. These results highlight that the combination of effective instructional leadership, a strong collaborative culture, and high teacher self-efficacy is essential in improving the quality of education at the junior high school level. Abstrak Penelitian ini dilatarbelakangi oleh pentingnya peran guru dalam menentukan mutu pendidikan di sekolah, yang sangat dipengaruhi oleh kepemimpinan kepala sekolah, budaya kolaboratif, serta keyakinan diri guru. Tujuan penelitian ini adalah untuk menganalisis pengaruh kepemimpinan instruksional kepala sekolah, professional learning community (PLC), dan efikasi diri terhadap kinerja guru SMP Negeri di Kecamatan Banjarmasin Timur. Penelitian menggunakan pendekatan kuantitatif dengan desain korelasional. Populasi penelitian terdiri dari 227 guru, dengan sampel yang diperoleh melalui proportional random sampling. Instrumen penelitian berupa angket skala Likert yang telah diuji validitas dan reliabilitasnya. Data dianalisis menggunakan regresi linier berganda, analisis jalur, serta uji Sobel untuk menguji peran mediasi. Hasil penelitian menunjukkan bahwa kepemimpinan instruksional, PLC, dan efikasi diri berpengaruh signifikan terhadap kinerja guru, baik secara parsial maupun simultan. Efikasi diri terbukti menjadi faktor psikologis yang memperkuat peran kepemimpinan instruksional dan PLC dalam meningkatkan kinerja guru. Temuan ini menegaskan bahwa kombinasi antara kepemimpinan instruksional yang efektif, budaya kolaboratif yang kuat, dan efikasi diri guru yang tinggi merupakan kunci dalam upaya peningkatan mutu pendidikan di sekolah menengah pertama. Kata Kunci: efikasi diri; kepemimpinan instruksional; kinerja guru; professional learning community